Medical Utilization of Kiosks in the Delivery of Patient Education: A Systematic Review - Roxanne Nagurka; Suzanne Bentley; Edgardo Ordonez; William Sproule (Tabriz University of Medical Sciences, 2014)
Background: The utilization of kiosks has previously been shown to be effective for collecting information, delivering educational modules, and providing access to health information. We discuss a review of current literature for the utilization of kiosks for the delivery of patient education. Methods: The criteria for inclusion in this literature review were: (1) study dis-cusses the utilization of kiosks for patient health education; (2) study discusses the use of touch screens for patient health information; (3) published in English. Our review includes searches via MEDLINE databases and Google Scholar for the years 1996-2014. Results: Overall, 167 articles were screened for final eligibility, and after discarding duplicates and non-eligible studies with abstract. Full-text review of 28 articles was included in the final analysis. Conclusion: The review of available literature demonstrates the effectiveness of touch screen kiosks to educate patients and to improve healthcare, both at a performance and cost advantage over other modes of patient education.